Preparation and characterization of biodegradable rigid polyurethane foams from the liquefied eucalyptus and pine woods - Ertas, Murat; Fidan, Muhammed Said; Alma, Mehmet Hakki D.L.D.A.L. (Statny Drevarsky Vyskumny Ustav sdvu4@computel.sk, 2014)
In this study, eucalyptus (Eucalyptus camaldulensis L.) and pine (Pinus sylvestris L.) woods were liquefied using the the blended solvents mixture of polyethylene glycol PEG-400/glycerin in the presence of sulfuric acid as a catalyst at 140-160°C for 120 min. The insoluble parts in the liquefied eucalyptus and pine were found as 17.8 and 5.5 wt. %, respectively. The acid and hydroxyl numbers of the liquefied eucalyptus and pine were determined and compared with each other. Polyurethane-type rigid foams (RPUFs) were successfully prepared by a co-polymerization of the liquefied woods (LWs) and polymeric methylene diphenylene diisocyanate (PMDI). The compressive strength (120 to 250 kPa), the modulus of elasticity (1 to 6 MPa), the density (20 to 50 kg.nr-3) and thermal conductivity (0.0352 to 0.0374 W.mK -1) of the RPUFs prepared from the LWs were found to be almost comparable to those of the synthetic foams. Furthermore, the biodegradability of the biomass-based foams was higher than that of the synthetic ones.
Keywords: Biodegradable; Biomass; Eucalyptus camaldulensis; Liquefaction; Pinus sylvestris; Polyurethane foams